Alumni Job Networks at Elite Universities and the Efficacy of Affirmative Action - Cecilia Machado; Germán Reyes; Evan Riehl (Institute of Labor Economics (IZA), 2022)
We examine the efficacy of affirmative action at universities whose value depends on peer and alumni networks. We study an elite Brazilian university that adopted race- and income-based affirmative action at a large scale. Using employer-employee data, we show that a key benefit of attending the university is access to high-paying jobs affiliated with its alumni. Affirmative action increased disadvantaged students' access to these firms and raised their early-career earnings. But these benefits faded over time. Further, the increase in student body diversity lowered the job prospects and earnings of the school's most highly ranked students.
Keywords: I23; I26; J31; 330; affirmative action; alumni network; higher education